An Analysis of Moral Values Found in a Korean TV Series 'The World of Married' - Fitria, Tira Nur (LPPM Universitas Advent Indonesia, 2020)
Being released in 2020, “The World of Married” drama entails certain life-lessons that are seriously heart-touching. For all the lovers of Korean drama in the form of TV series, it has some of the life-lessons or moral values taught in the story. Therefore, the objective of this study is to find out the moral values or messages in “The World of Married”. This research uses qualitative research. The analysis shows that In “The World of Married”, contains some moral value, they are 1) there is no perfect family life. 2) honesty is the key to family life. 3) having principles in choosing or deciding something. 4) having loyalty with a partner and not having an affair with another. 5) selecting in choosing the best friend. 6) loving the Wrong Person (Love is blind). 7) all decisions have risks. 8) an act of revenge is not the best solution. 9) avoiding violence in the family. Moral values in the movie can be understood as one base on which people make decisions whether they do is right or wrong. It also implicates what have to do or not to do in their life. 10) children become victims of the problems and divorce of parents.